ANALISIS GANGGUAN PERFORMA RADAR SAAT BERNAVIGASI DI PERAIRAN BUNATI - Heronimus Emilianus Nida; Oktavera Sulistiana; Agriani Pongkessu (STKIP Subang, 2026)
The S-Band radar is a primary navigational instrument used onboard ships to detect surrounding objects and support decision-making, particularly in low-visibility conditions. In practice, radar performance may degrade due to sensor failures or integration issues within the ship’s Integrated Bridge System (IBS). This study aims to analyze the factors causing performance disruption of the S-Band radar on MV Golden Rose while navigating in Bunati Waters, as well as to evaluate the compliance of the radar’s Planned Maintenance System (PMS) with the maintenance schedule.The findings reveal that the radar malfunction was triggered by simultaneous loss of essential sensor inputs—such as heading (HDG), speed through water (STW), Automatic Identification System (AIS), and unstable GPS data. Initial troubleshooting identified moisture on RS-422 connectors, possible corrosion, and component degradation due to aging. The study also found discrepancies between scheduled and actual maintenance activities, notably delayed antenna inspections.Overall, the degradation of radar performance is more dominantly caused by internal system deterioration, as indicated by corrosion and oxidation on navigation sensor connectors, instability in the power supply, and the gradual loss of sensor inputs as recorded in the radar operation logs caused by insufficient preventive maintenance and deteriorating hardware integrity. These findings highlight the need to strengthen radar maintenance procedures and improve sensor integration management to ensure safer navigation.